Performance of cucumber hybrids cultivated in coconut fiber and soil - Castoldi,Renata (2014)
The objective of this work was to evaluate the performance of three Japanese group cucumber hybrids, which were cultivated in two cultivation systems. The experiment was designed in a split-plot randomized block design with two cultivation systems (coconut fiber and soil) for commercial Japanese cucumber hybrids ('Tsuyataro', 'Yoshinari' and 'Nankyoku'). After harvesting the cucumbers, we evaluated the number of marketable fruits per plant, the average fruit length, the mean fruit diameter, the bottom fruit diameter, the marketable production of fruits per plant and the marketable yield per hectare. There were significant interactions between the cultivation system and the hybrid, as indicated by the number of marketable fruits. The Nankyoku hybrid had the highest average (14.54 fruits pl-1), although it did not differ from the Yoshinari hybrid when grown in coconut fiber. In soil culture, the Yoshinari hybrid had the highest average number of fruits per plant (10.12 fruits pl-1) and did not differ from the Tsuyataro hybrid. Cultivation in coconut fiber provided better results for production traits and plant productivity. 'Yoshinari' and 'Nankyoku' were the most productive hybrids. Based on the cucumber cultivation results from a protected environment, the cultivation of hybrid Japanese cucumbers and Yoshinari and Nankyoku hybrids in coconut fiber is recommended.